Adult Mortality in Russian Rural Areas: Inter-regional Comparisons - Tatiana Blinova; Svetlana Bylina (European Regional Science Association (ERSA), 2011)
Regions of the Russian Federation draw up purpose-oriented programs aiming at improving the health and reducing the mortality among the population. The task of decreasing the mortality among the rural population, especially overcoming the phenomenon of "excess mor-tality" among the people of the able-bodied age, is considered a priority in the federal and re-gional programs for social-economic development for the nearest future. In view of this, the task of this research is to develop taxonomy of regions of RF according to the structure of mortality among their rural population, analyze the inter-regional comparisons and regression equations that include demographic, economic, social and ecological explanatory variables for different types of the regions. The paper presents a comparative analysis of mortality structure dynamics for urban and rural population of RF. The inter-regional comparisons of the Russian rural mortality structure are made. The inter-regional differentiation in terms of the level of mortality of the population and the differences between the city and the countryside are substantiated by using a set of causes and factors of both demographic and social-economic nature. For the purpose of making a deeper analysis of the territorial aspects of rural mortality, the rural territories are classified according to the structure of mortality from basic causes of death. The description of the territorial features of mortality determinants for the regions of each typological group is given. The structure of the classification groups and average parameter values are presented in the form of cartograms and tables. The regression equations including the demographic, economic, social and ecological explanatory variables are considered for both the entire RF and different types of its regions. The models derived are described from the viewpoint of significance of the influence the chosen parameters produce on the level of mortality among the rural population belonging to each classified group of the regions. The territorial features of causes of death identified in the course of the research should be taken into account when substantiating regional programs aiming to de-crease the rural mortality and increase the life expectancy, as well as when drawing up and implementing rural social development programs.
Keywords: 330